The role of lactoferrin in the treatment of upper respiratory tract infections - Cąkała, Marlena; Kozioł, Magdalena; Błaszczak, Karolina; Podgórniak, Kamila; Piotrowska, Julia; Skotnicka, Joanna; Zajkowska, Aleksandra; Witkowska, Maria (Quality in Sport, 2024)
Introduction Lactoferrin is a glycoprotein belonging to the group of transferrins found in most body fluids. It has been shown to possess antimicrobial, anti-inflammatory, immunomodulatory and anticancer properties. The increasing availability and widespread use of dietary supplements containing lactoferrin have been observed as supportive measures in managing various infections. Aim of the study The objective of this study is to summarize the current knowledge regarding the anti-infective - mostly antiviral - effects of lactoferrin and the justification for its use in the treatment of upper respiratory tract infections. Knowledge summary Scientific research has consistently confirmed the effectiveness of lactoferrin against pathogenic microorganisms. The antibacterial effect of this protein is based mainly on the management of available iron resources - an ingredient necessary for bacterial growth. On the other hand, the antiviral activity of this protein is based on the induction of interferon production. Conclusion Dietary supplements containing lactoferrin are approved by the US Food and Drug Administration (FDA) for supportive use in infections. Lactoferrin exhibits antimicrobial activity supported by research in specific infections. It has a good tolerance and safety profile, therefore it seems that it can be used adjunctively in this indication.